Controlling and co-ordinating chitinase secretion in a Serratia marcescens population. Issue 11 (17th September 2019) - Costa, Marília de Assis Alcoforado; Owen, Richard A.; Tammsalu, Triin; Buchanan, Grant; Palmer, Tracy; Sargent, Frank
Abstract : Serratia marcescens is a γ-Proteobacterium and an opportunistic animal and insect pathogen. The bacterium exhibits a complex extracellular protein 'secretome' comprising numerous enzymes, toxins and effector molecules. One component of the secretome is the 'chitinolytic machinery', which is a set of at least four chitinases that allow the use of insoluble extracellular chitin as sole carbon source. Secretion of the chitinases across the outer membrane is governed by the chiWXYZ operon encoding a holin/endopeptidase pair. Expression of the chiWXYZ operon is co-ordinated with the chitinase genes and is also bimodal, as normally only 1% of the population expresses the chitinolytic machinery. In this study, the role of the ChiR protein in chitinase production has been explored. Using live cell imaging and flow cytometry, ChiR was shown to govern the co-ordinated regulation of chiWXYZ with both chiA and chiC . Moreover, overexpression of chiR alone was able to increase the proportion of the cell population expressing chitinase genes to >60 %. In addition, quantitative label-free proteomic analysis of cells overexpressing chiR established that ChiR regulates the entire chitinolytic machinery. The proteomic experiments also revealed a surprising link between the regulation of the chitinolytic machinery and the production of proteins involved in the metabolism of nitrogen compounds such as nitrate and nitrite. The research demonstrates for the first time that ChiR plays a critical role in controlling bimodal gene expression in S. marcescens, and provides new evidence of a clear link between chitin breakdown and nitrogen metabolism.